Potentiating Effect of Adenosine on Other Inhibitors of Platelet Aggregation - Murakami, M.; Odake, K.; Takase, M.; Yoshino, K. (Thrombosis and Haemostasis, 1972)
Adenosine was rapidly incorporated into human platelets, and the inhibitory effect of adenosine on platelet aggregation was correlated with the incorporation process. Adenosine potentiated the inhibitory action of other inhibitors, such as dipyridamole, prostaglandin E1 and Y-3642. The inhibition of aggregation was associated with the preservation of platelet adenine nucleotides and the prevention of ADP release. On the other hand, the radioactive adenine nucleotide pattern of platelets was not substantially affected by inhibitors. The relation of inhibition of aggregation with ADP release was discussed.